Improving the procedure of environmental audit of oil and gas facilities and industrial enterprises - Мойсеєнко, Олена Володимирівна; Заячук, Ярослав Іванович; Мойсеєнко, Микола Іванович (Eastern-European Journal of Enterprise Technologies, 2014)
As a result of a systems analysis of economic activity of enterprises, the procedure for environmental impact reduction or prevention is proposed, which, at the stages of making and implementing decisions allows not to interfere with performing production functions of industrial facility, provide analysis of the results achieved and adjust its activity according to the results achieved. By carrying out the analysis and comparison of each stage of the conventional procedure for the environmental impact assessment (EIA) with the proposed stages of impact reduction or prevention, it was found that they coincide. The specificity of the EIA procedure lies in selecting methods in conditions of implementing individual stages of the procedure. In terms of the systems analysis, the environmental audit procedure corresponds to the EIA procedure and, in turn, to the proposed procedure for environmental impact reduction or prevention. The analogy between the objectives and procedures of the EIA and environmental audit (EA) has allowed to use expert decision support methods and EIA experience with specific modification during the EA. As a result, the improved EA procedure in terms of the environmental impact minimization, which during the EA provides higher probability and effectiveness of analysis, increases the efficiency of the auditors is developed.